In vitro and in vivo evidence for orphan nuclear receptor RORα function in bone metabolism - Meyer, Thomas (The National Academy of Sciences, 2000)
Bone is a major target site for steroid hormone action. Steroid hormones like cortisol, vitamin D, and estradiol are responsible for principal events associated with bone formation and resorption. Over the past decade, new members of the nuclear hormone gene family have been identified that lack known ligands. These orphan receptors can be used to uncover signaling molecules that regulate yet unidentified physiological networks. In the present study the function of retinoic acid receptor-related orphan receptor (ROR) α in bone metabolism has been examined. We showed that RORα and RORγ, but not RORβ, are expressed in mesenchymal stem cells derived from bone marrow. Interestingly, for RORα we observed an increased messenger signal expression between control cells and cells undergoing osteogenic differentiation. Furthermore, the direct activation of mouse bone sialoprotein by RORα, typically 7-fold, has been shown. In contrast, transient overexpression of RORα overrides the activation of the osteocalcin promoter by 1α,25-dihydroxyvitamin D(3). In addition, we have investigated bone mass parameters and bone geometry in the mouse mutant staggerer (sg/sg), a mouse strain that carries a deletion within the RORα gene. Homozygote mutants have thin long bones compared with the heterozygote animals and wild-type littermates. More interestingly, the bones of the sg/sg animals are osteopenic as indicated by the comparison of bone mineral contents of sg/sg animals to the heterozygote and wild-type animals. We conclude that these in vitro and in vivo results suggest a function for RORα in bone biology. RORα most likely acts by direct modulation of a bone matrix component.